Impact of temperature and relative humidity on the near infrared spectroscopy measurements of cotton fiber micronaire. Issue 20 (October 2018) - Zumba, Jimmy; Rodgers, James; Indest, Matthew
A key cotton fiber property is micronaire. Micronaire can impact the fiber's quality, textile processing efficiency, and fabric dye consistency. Fiber micronaire is normally measured in a laboratory under tight standard temperature and relative humidity (RH) environmental conditions (21 ± 1℃, 65 ± 2% RH). Near infrared (NIR) measurements have been performed both inside and outside of the laboratory, but measurements outside the laboratory have at times demonstrated reduced predictive capability, possibly due to the lack of standard environmental conditions. A program was implemented to determine the impact of non-standard conditions of temperature T and relative humidity RH on NIR micronaire results for bench-top and portable NIR instruments. Non-standard T and RH resulted in varying fiber moisture, which impacted the NIR spectral response. The NIR micronaire results were impacted by the non-standard conditioning for all instruments, with the lower wavelength region (∼910–1680 nm) portable instrument impacted the most. The impacts and deviations were greater at high temperature/RH compared to low temperature/RH conditioning. These results provide a rationale for the deviations observed previously in NIR micronaire results for outside the laboratory micronaire measurements with portable NIR units.